2018
DOI: 10.1021/acs.jmedchem.8b00971
|View full text |Cite
|
Sign up to set email alerts
|

Novel Hypoxia-Inducible Factor 1α (HIF-1α) Inhibitors for Angiogenesis-Related Ocular Diseases: Discovery of a Novel Scaffold via Ring-Truncation Strategy

Abstract: Ocular diseases featuring pathologic neovascularization are the leading cause of blindness, and anti-VEGF agents have been conventionally used to treat these diseases. Recently, regulating factors upstream of VEGF, such as HIF-1α, have emerged as a desirable therapeutic approach because the use of anti-VEGF agents is currently being reconsidered due to the VEGF action as a trophic factor. Here, we report a novel scaffold discovered through the complete structure−activity relationship of ring-truncated deguelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“… 33 SAR studies identified the latter as promising candidates for HIF-1α inhibitors. 34 One of those analogues, SH-1242, further inhibits Hsp90 activity and shows potent anticancer efficacy. 35 We could demonstrate the applicability of this method for benzylation of selected substrates using BnMe 3 NCl as a benzylating agent.…”
Section: Resultsmentioning
confidence: 99%
“… 33 SAR studies identified the latter as promising candidates for HIF-1α inhibitors. 34 One of those analogues, SH-1242, further inhibits Hsp90 activity and shows potent anticancer efficacy. 35 We could demonstrate the applicability of this method for benzylation of selected substrates using BnMe 3 NCl as a benzylating agent.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been shown to inhibit tube formation of human umbilical vein endothelial cells (HUVECs) and in vivo angiogenesis of chick chorioallantoic membrane [174], which is consistent with deguelin antiangiogenic activity. In addition, deguelin analogs have been recently produced which inhibit HIF-1α and reduce both in vitro angiogenesis and neovascularization in the OIR model [176].…”
Section: Nutraceuticals and Vascular Changesmentioning
confidence: 99%
“…Next, various 7-amino chromones were obtained in two more steps. The 7-hydroxyl group was first functionalized with trifluoromethanesulfonic anhydride (Tf 2 O) under aqueous conditions to yield the triflate, followed by the synthesis of the desired amine derivative. 7-Primary amine chromone analogues were obtained by removing benzophenone oxime in acidic conditions after palladium-catalyzed Buchwald–Hartwig coupling reactions of triflate with benzophenone imine.…”
Section: Resultsmentioning
confidence: 99%
“…7-Ethylamino chromone analogues were obtained by N-monoalkylation of a primary amine with alkyl halides. 7-Tertiary amine chromone analogues were synthesized by palladium-catalyzed Buchwald–Hartwig reactions of triflate with the corresponding amines in the presence of palladium acetate. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation